Pengaruh Model Pembelajaran Jigsaw Terhadap Peningkatan Hasil Belajar Sejarah Pendidikan Agama Kristen - Manuain, Leryani Mince Maria; Alexander, Ferdinant; Rantesalu, Marsi Bombongan (Universitas Persatuan Guru 1945 NTT, 2018)
This research aims to find the influence of applying cooperative learning jigsaw type to improve the learning outcomes of the 6th semester students in the course of History of Christian Religious Education at STAKN Kupang in 2017. Quantitative research methods with the quasi experiment nonequeivalent control group design approach was used as a research method. The experimental study involved two groups of students, the experimental group and the control group, each of which was given pre-test and post-test. The target population of 62 students was divided into two different groups. Each consisted of 32 students in the experimental group and 30 students in the control group. The results showed that the application of cooperative learning jigsaw type was able to improve students’ learning outcomes at 30.625 or 30.6 persen with significance value on the sig. value (2-tailed) by 0.000 <0.05 or there is a significant increase. The average value of students’ learning outcomes using cooperative learning model with jigsaw approach is greater than 8.586 with significance value at sig. value (2-tailed) of 0.003 <0.05, which means that there is a significant difference in the value of learning outcomes compared to that of students using only conventional methods such as lectures